Ética de la investigación en salud y su relación con la pobreza - Perales Cabrera, Alberto (2003)
Considering health as a closely related concept to the one of development, either of the individual, people or nations, the author postulates that research is not an exclusive scientifie and concrete type of work but one that is carried out within a wide social context in which economic and political factors as well as power relationships, either at institutional or national level, models its type, real practice and results publication. In that sense, research, besides advancing our knowledge, must always fulfill an essential ethical social aim for the benefit of man and humankind; and, in third word countries, as it is the case of Peru, to consider poverty (which he divides into two types: with and without culture of poverty) in its design poverty as a valid co-causal variable in many health problems. In this perspective, besides reviewing the ethic criteria of clinical research, the author analyzes the ethical conflict of Peruvian researchers, pointing out the need to develop methodologies that would allow a better ethical control of their scientific behavior "fromtheir inner world allow" because the deonthologic strategies have not proved themselves efficacious.